2022
DOI: 10.1093/mtomcs/mfac101
|View full text |Cite
|
Sign up to set email alerts
|

63Cu(I) binding to human kidney 68Zn7-βα MT1A: determination of Cu(I)-thiolate cluster domain specificity from ESI-MS and room temperature phosphorescence spectroscopy

Abstract: Mammalian metallothioneins (MTs) are important proteins in Zn(II) and Cu(I) homeostasis with the Zn(II) and Cu(I) binding to the 20 cysteines in metal-thiolate clusters. Previous electrospray ionization (ESI) mass spectrometric analyses of Cu(I) binding to Zn7-MT were complicated by significant overlap of the natural abundance isotopic patterns for Zn(II) and Cu(I) leading to impossibly ambiguous stoichiometries. In this paper, isotopically pure 63Cu(I) and 68Zn(II) allowed determination of the specific stoich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(35 citation statements)
references
References 82 publications
2
33
0
Order By: Relevance
“…These results are in line with those from the Stillman group, who studied Cu­(I) binding to apoMT1a and showed that the α-domain binds four Cu­(I) ions, while the β-domain binds six Cu­(I), forming copper-thiolate clusters. , In their recent research, they showed that Cu­(I) (not Cu­(II)) binds to Zn 7 MT3 forming multiple species, with no preference for Cu 4 Zn 4 MT3 . In another study, Melenbacher et al studied Cu­(I) binding to Zn 7 MT1a instead of apoMT1a . Their results suggested the formation of two main complexes, βZn 1 Cu 5 αZn 4 MT1a and βCu 6 αZn 4 MT1a.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…These results are in line with those from the Stillman group, who studied Cu­(I) binding to apoMT1a and showed that the α-domain binds four Cu­(I) ions, while the β-domain binds six Cu­(I), forming copper-thiolate clusters. , In their recent research, they showed that Cu­(I) (not Cu­(II)) binds to Zn 7 MT3 forming multiple species, with no preference for Cu 4 Zn 4 MT3 . In another study, Melenbacher et al studied Cu­(I) binding to Zn 7 MT1a instead of apoMT1a . Their results suggested the formation of two main complexes, βZn 1 Cu 5 αZn 4 MT1a and βCu 6 αZn 4 MT1a.…”
supporting
confidence: 83%
“…38 In another study, Melenbacher et al studied Cu(I) binding to Zn 7 MT1a instead of apoMT1a. 39 Their results suggested the formation of two main complexes, βZn 1 Cu 5 αZn 4 MT1a and βCu 6 αZn 4 MT1a. Furthermore, in the presence of excess glutathione (GSH), Austin and co-workers reported, based on ITC analysis, that Zn 7 MT2 and Zn 7 MT3 can form Cu(I) 4 -thiolate clusters, resulting in βCu 4 αCu 4 MT2 ox and βCu 4 αCu 4 MT3 ox .…”
mentioning
confidence: 99%
“…Phosphorescence has long been used to identify the presence of Cu(I)-thiolate clusters in MTs [63]. Both room temperature and 77 K emission data have been reported [35,[52][53][54]59,60,[62][63][64][65][66]. Emission spectra are often measured at 77 K as the metal-dependent charge transfer band blue shifts from ~700 nm (room temperature) to ~500-600 nm and intensifies at low temperatures (77 K).…”
Section: Use Of Emission Spectroscopymentioning
confidence: 99%
“…Some of the above-mentioned reports do include ESI-MS data [52,53]. However, due to the overlapping naturally abundant isotopes of Cu(I) and Zn(II) (Table 1) and the broad nature of the metallothionein protein peak, it is essentially impossible to determine accurate Cu, Zn-MT stoichiometries using natural abundance Cu(I) and Zn(II) ions [62]. As such, many studies on Cu, Zn-MTs that do include ESI-mass spectral results tend to only report the total number of metals bound to the protein because the data cannot discriminate between the relative fractions of Cu(I) and Zn(II) [70][71][72].…”
Section: Advantage Of Isotopes In Esi-msmentioning
confidence: 99%
See 1 more Smart Citation